Strategic Cost Management Practices and Their Role in Competitive Advantage (gjstudies, 2022)
The pursuit of competitive advantage remains the central preoccupation ofstrategic management. Traditionally, cost leadership, as articulated by Porter(1985), has been conceived as a generic strategy achieved through scale, efficiency, and tight control of overhead. However, this static view is increasinglyinadequate in hyper-competitive, digitally-mediated markets where cost structures are fluid and competitive moves are rapidly iterated. This paper arguesfor a fundamental reconceptualization of strategic cost management (SCM). Weposit that SCM is not a defensive, inwardly-focused activity aimed at minimization, but a proactive, strategic capability to shape industry cost norms andcreate asymmetrical competitive positions. Our novel contribution lies in synthesizing frameworks from computational game theory, behavioral economics,and cybersecurity resilience to model SCM as a dynamic, multi-player game ofstrategic interaction.